Representasi Nilai-nilai Spiritual dalam Novel Rembulan Tenggelam di Wajahmu Perspektif Pendidikan Islam - Nicky Estu Putu Muchtar; Novia Shinta Kamaliyah (JOM, 2026)
This study examines the representation of spiritual values ​​in Tere Liye's novel "Rembulan Tenggelam di Wajahmu" from the perspective of Islamic education. This study aims to identify the spiritual values ​​contained in the novel, analyze how these values ​​are represented through the plot, characters, and narrative, and examine their relevance to Islamic education. This study uses a qualitative approach with a content analysis method. The primary data are sourced from the novel, while supporting data are obtained from relevant literature. The results show that the novel's spiritual values ​​reflect the four main virtues according to Ibn Miskawaih: wisdom, courage, iffah, and justice. These values are represented through the characters' life journeys, which illustrate the process of spiritual maturation. In addition, these values ​​are relevant to Islamic education, particularly in the formation of faith, morals, intellectual awareness, and social responsibility.